Indigenous microflora on alfalfa and corn, and population changes during ensiling - Lin, C.; Hart, R.A.; Bolsen, K.K.; Dickerson, J.T.; Curtis, J.L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Lactic acid bacteria (LAB), Enterobacteriaceae, yeasts, molds, and lactate-using yeasts were examined on four cuttings of alfalfa, each at three maturity stagest and three com hybrids in 1989. In addition, microflora population changes were traced during ensiling for the second and fourth cutting alfalfas and the three com hybrids. Enterobacteriaceae were predominant on alfalfa; yeasts, molds, and Enterobacteriaceae predominated on com. Higher proportions of lactate-using yeast were found on com than alfalfa. Lactic acid bacteria comprised a small (104 to 105 CFU/g) proportion of the total (lot») populations, with streptococci the main indigenous LAB group. Lactobacilli, pediococci, and leuconostoc were the minor groups, and their occurrence was variable, particularly on alfalfa. Cutting and maturity of alfalfa did not have a significant effect on the indigenous microflora. The chopping process significantly increased the numbers of microorganisms, but wilting alfalfa did not affect the populations. Once the crops were ensiledt LAB grew extremely fastt and reached maximum numbers at 3 d post-ensiling. Yeast and mold counts showed a continuous reduction as ensiling progressed, and this was much more pronounced in alfalfa than corn.
Keywords: Beef; Alfalfa; Corn; Microflora; Silage